(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article discusses the experiment of inducing mutations in seed and drupe plants using X-rays, the results and scientific news, the effect of different doses of radiation on growth, and the selected promising varieties.